2020
DOI: 10.1111/vox.13020
|View full text |Cite
|
Sign up to set email alerts
|

Ovine red cell concentrates for transfusion research – is the storage lesion comparable to human red cell concentrates?

Abstract: Background and objectives Sheep are increasingly being used as a large in vivo animal model of blood transfusion because they provide several advantages over small animals. Understanding the effects of storage duration on ovine (ov) red cell concentrates (RCCs) and how these changes compare with stored human (hu) RCCs is necessary to facilitate clinical translation of research findings.Materials and methods OvRCCs (n = 5) collected and processed in standard human blood collection packs, and equivalent huRCCs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Slower metabolic rates in mature porcine erythrocytes compared to other mammalian red blood cells were also observed in a study by Dixon et al [74]. As pointed out in a recent publication by Simonova and colleagues, major differences in erythrocyte metabolism were also detected between ovine and human-packed red blood cells [63]. Especially maximum activity of glucose-6-phosphate dehydrogenase (G-6-PD), which serves an important role in protection against oxidative damage and glycolysis, was noticeably lower than in human erythrocytes [63,75,76].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Slower metabolic rates in mature porcine erythrocytes compared to other mammalian red blood cells were also observed in a study by Dixon et al [74]. As pointed out in a recent publication by Simonova and colleagues, major differences in erythrocyte metabolism were also detected between ovine and human-packed red blood cells [63]. Especially maximum activity of glucose-6-phosphate dehydrogenase (G-6-PD), which serves an important role in protection against oxidative damage and glycolysis, was noticeably lower than in human erythrocytes [63,75,76].…”
Section: Discussionsupporting
confidence: 59%
“…Ovine and canine transfusion models included in this scoping review reported no data in this regard but generally described lower 2,3-diphosphoglycerate levels in ovine red blood cell units compared to humans in a previously published study by Baron et al [62]. Corresponding reductions of 2,3-diphosphoglycerate, glucose and adenosine triphosphate levels in ovine-packed red blood cells throughout storage were also reported in a recent study by Simonova et al [63]. The depletion of adenosine triphosphate levels in porcine-packed red blood cells occurred more rapidly than those reported in human units [22,25,26].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations